Causality-Free Modeling of a Wind Turbine with Open-loop and Closed-loop Validation Results. Issue 37 (2022) - Mohsin, Kazi; Odeh, Mohammad; Ngo, Tri; Das, Tuhin
Abstract: This article presents the development of the Control-oriented, Reconfigurable, and Acausal Floating Turbine Simulator (CRAFTS). CRAFTS is a library-based, modular, hierarchical model architecture that enables rapid and accurate simulation of wind turbines. The architecture of CRAFTS facilitates the incorporation of model-based system reconfiguration features to simulate multiple design variants. CRAFTS also supports the integration of models developed on a causality-free platform (e.g. Modelica®) with existing causal models. Numerous test cases are devised to show that CRAFTS has similar performances as the validated and industry-standard platform OpenFAST.